The relationship between blastocyst morphology, chromosomal abnormality, and embryo gender. - Alfarawati, S; Fragouli, E; Colls, P; Stevens, J; Gutiérrez-Mateo, C; Schoolcraft, W; Katz-Jaffe, MG; Wells, D (2011)
OBJECTIVE: To assess correlation between blastocyst morphology and chromosomal status. DESIGN: Observational research study. SETTING: An IVF clinic and a specialist preimplanation genetic diagnosis (PGD) laboratory. PATIENT(S): Ninety-three couples undergoing IVF treatment in combination with chromosome screening of embryos. INTERVENTION(S): Five hundred blastocysts underwent trophectoderm biopsy and comprehensive chromosome screening using comparative genomic hybridization (CGH). The morphology of the embryos was evaluated using standard methods. MAIN OUTCOME MEASURE(S): Association of aneuploidy and morphologic score. RESULT(S): A total of 56.7% of blastocysts were aneuploid. One-half of the grade 5/6 blastocysts were euploid, compared with only 37.5% of embryos graded 1/2, suggesting an effect of aneuploidy on blastocyst development. Aneuploidy also had a negative effect on inner cell mass and trophectoderm grades. Morphologically poor blastocysts had a higher incidence of monosomy and abnormalities affecting several chromosomes. The gender ratio was significantly skewed in relation to morphology. A total of 72% of blastocysts attaining the highest morphologic scores (5AA and 6AA) were found to be male, compared with only 40% of grade 3 embryos. CONCLUSION(S): Morphology and aneuploidy are linked at the blastocyst stage. However, the association is weak, and consequently, morphologic analysis cannot be relied on to ensure transfer of chromosomally normal embryos. A significant proportion of aneuploid embryos are capable of achieving the highest morphologic scores, and some euploid embryos are of poor morphology. Gender was associated with blastocyst grading, male embryos developing at a significantly faster rate than females.